Sol- gel synthesis of Ga2O3 nanorods and effect of precursor chemistry on their structural and morphological properties. Issue 16 (November 2018) - Gopal, Ram; Goyal, Ankit; Saini, Ajay; Nagar, Meena; Sharma, Nikita; Gupta, Deepak Kumar; Dhayal, Veena
Abstract: Synthesis of mono-crystalline Ga2 O3 Nanorods was done by sol-gel transformation of gallium(III) isopropoxide (Ga(OPr i )3 ). XRD studies were done to determine the planes and crystal structure of synthesized nanorods that showed the synthesis of β-Ga2 O3 (a) . TEM studies of synthesized Ga2 O3 confirmed the synthesis of monocrystalline β-Ga2 O3 nanorods. To study the effect of precursor chemistry and to determine role of precursor structures on the crystal structure, phase and morphology of the Ga2 O3, a new modified precursor complex was synthesized. The reaction of Ga(OPr i )3 with N-phenylsalicylaldimine, [C6 H4 (OH)CH=N(C6 H5 )] in 1:1 M ratio yielded [(H5 C6 )N = CH-C6 H4 OGa(OPr i )2 ]. The newly synthesized complex was characterized by elemental analyses, molecular weight measurement, FT-IR and NMR ( 1 H and 13 C) spectral studies. Spectral studies of the modified complex suggest the presence of bi-dentate mode of attachment of Schiff's base in the solution state. Sol-gel transformations of [(H5 C6 )N = CH-C6 H4 OGa(OPr i )2 ] in organic medium, yielded γ-Ga2 O3 (b ), as found by XRD studies. TEM image of the sample (a ) revealed the formation of nano-rods of oxide with average diameter of 100 nm whereas the TEM image of sample (b ) showed presence of nano-sized particles of oxide with average particle size of 10 nm. Morphological and compositional studies of synthesized samples (a) and (b) were carried out using SEM and EDX. The method provides a possibility of large scale synthesis of dissimilar shaped and pure Ga2 O3 nanoparticles.